Analysis Of The Meaning Of Boraspati Philosophy As A Cultural Symbol Of The Simalungun Batak Society (Semiotic Study) - Siahaan, Meilina; Sirait, Jumaria; Saragih, Vita Riahni; Siregar, Junifer; Silitonga, Immanuel Doclas Belmondo (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to determine the Analysis of the Philosophical Meaning of Boraspati as a Cultural Symbol of the Batak Simalungun Community (Semiotic Study). Based on the results of research conducted by researchers regarding the Boraspati symbol in the culture of the Batak Simalungun community reviewed from the semiotic study of Charles Sanders Peirce, it can be concluded that Boraspati is a traditional symbol that has a deep philosophical meaning and does not merely function as an ornament or visual decoration. The Boraspati symbol represents the outlook on life, belief system, and social structure of the Simalungun community which is full of local wisdom values. Through a semiotic approach, Boraspati is understood as a cultural sign that contains moral and spiritual messages, which depicts a harmonious relationship between humans, nature, and the Creator. The results of this study indicate that each symbolic element in Boraspati reflects the ethics of life, social order, and cultural identity of the Simalungun community which is passed down from generation to generation